2019
DOI: 10.1136/svn-2019-000302
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical thrombosis: the dark side of force and dawn of mechano-medicine

Abstract: Arterial thrombosis is in part contributed by excessive platelet aggregation, which can lead to blood clotting and subsequent heart attack and stroke. Platelets are sensitive to the haemodynamic environment. Rapid haemodynamcis and disturbed blood flow, which occur in vessels with growing thrombi and atherosclerotic plaques or is caused by medical device implantation and intervention, promotes platelet aggregation and thrombus formation. In such situations, conventional antiplatelet drugs often have su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 179 publications
(306 reference statements)
1
29
0
Order By: Relevance
“…The follow-up studies suggested that γ 0 , S and α affect platelet aggregation in terms of kinetics, stability and sizes of aggregates 38 . The underlying platelet mechanobiology at molecular and cellular levels is exciting yet incompletely understood 5 . One possibility is that a γ ′ threshold exists for VWF elongation, and its subsequent conformational activation 6 , 13 , 60 , 64 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The follow-up studies suggested that γ 0 , S and α affect platelet aggregation in terms of kinetics, stability and sizes of aggregates 38 . The underlying platelet mechanobiology at molecular and cellular levels is exciting yet incompletely understood 5 . One possibility is that a γ ′ threshold exists for VWF elongation, and its subsequent conformational activation 6 , 13 , 60 , 64 .…”
Section: Discussionmentioning
confidence: 99%
“…They become dangerous when they grow large and occlude blood vessels in the heart, brain and peripheral vascularized organs, leading to heart attack, stroke and deep vein thrombosis respectively 2 . While it is well known that platelet adhesion, activation, and subsequent aggregation play a central role in thrombosis, the interplay of biochemical and biomechanical factors regulating platelet thrombosis remains incompletely understood 3 5 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In arteries, red blood cells (RBCs) migrate to the centerline whereas platelets migrate towards the vessel wall, where they bind to the von Willebrand factor (vWF)-collagen cluster on top of a vessel lesion [ 3 ] or a ruptured atherosclerotic plaque. This process is supported by the irregular shape of platelets (which creates a surface that can be subjected to tangential shearing forces), by platelets sensing their mechanical environment [ 4 ], and by the linear conformation of vWF in high shear flow. This is also supported by RBCs pushing the platelets to aggregate closer together [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%